Development of a partnership between academia, community, and government in response to the 2022 mpox outbreak in Japan - KATO, Mio; YOSHIMATSU, Fumi; YAMAMOTO, Tomonori; KOBAYASHI, Nozomi; KIKUCHI, Tadashi; MATSUOKA, Saori; MATANO, Tetsuro; IWAHASHI, Kota; IKUSHIMA, Yuzuru; SHIONO, Satoshi; ISHIKANE, Masahiro; MORIOKA, Shinichiro; et al. (Nihon Koshu Eisei Zasshi(JAPANESE JOURNAL OF PUBLIC HEALTH), 2024)
Objectives　In response to the steady rise in the number of cases of mpox in nonendemic countries, starting with an outbreak in the United Kingdom in May 2022, the World Health Organization declared a public health emergency of international concern on July 23, 2022. As of November 13, 2022, seven cases of mpox have been reported in Japan.Methods　A community engagement approach was applied to prevent the spread of mpox in Japan.Results　A tripartite partnership between academia, community, and government (ACG) was established to promote multisectoral communication between vulnerable communities, medical personnel involved in diagnosis and treatment, public health specialists at public health centers, epidemiologists at the National Institute of Infectious Diseases (NIID), and government and public administration. Through information sharing, this ACG partnership can translate accurate information into effective infection control measures.Conclusion　By developing and maintaining the ACG partnership, an environment will be created that allows an immediate response to future public health crises affecting vulnerable communities. This Practice Report describes the process of establishing an ACG partnership.